The burden of mycobacteria species among children from postvaccination abscess in Southern India - Kannaiyan Kavitha; Latha Ragunathan; Paramasivam Elantheriyan; Kuppusamy Gopalakrishnan; Kumaraswamy Ajay Gopala; Indrajith Devandra Balamurugan; Ragunadha Reddy Navya; Sherin Samuel Marcella; Gobichettipalayam Kanniappan Venkatachalam (International Journal of Mycobacteriology, 2021)
Background: From the time vaccines were introduced, their impact has been beyond measurable. Mycobacteria are pathogens increasingly isolated from postvaccination abscess. Identification of these pathogens plays a very crucial role in the management of these babies. We aimed to determine Mycobacterial spp occurrence from vaccination abscess, draw local antibiogram, and guide management of babies with vaccination abscess. Methods: Babies with postvaccination abscess from 2016 to 2020 were included. Pus collected during incision and drainage was processed as per the standard guidelines. Mycobacterium isolates were identified by conventional methods, and all samples were confirmed by polymerase chain reaction. All babies underwent incision and drainage, and all were started with amoxicillin and clavulanic acid and changed later as per the sensitivity report. Results: Mycobacterium abscessus was isolated from 17% (12) pus samples from 71 postdiphtheria pertussis and tetanus vaccination, and Mycobacterium bovis was isolated from 83.3% (10) babies with post-Bacillus Calmette–Guérin vaccination. The mean interval between injection and abscess formation was 32.75 days in case of M. abscessus, whereas it was 50.4 days in case of M. bovis. All the M. abscessus were sensitive to linezolid, amikacin, and clarithromycin, whereas no treatment except incision and drainage was required for M. bovis. Conclusion: There is an increased incidence of Mycobacterial spp infection in postvaccination abscess. All babies with M abscessus responded well with combination antibiotic therapy plus drainage of abscesses, whereas M. bovis was treated by incision and drainage, and no further antibiotics were given.